2020
DOI: 10.18632/aging.102922
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing analysis of monocrotaline-induced PAH reveals dysregulated chemokine and neuroactive ligand receptor pathways

Abstract: Pulmonary arterial hypertension (PAH) is a serious disease characterized by elevated pulmonary artery pressure, inflammatory cell infiltration and pulmonary vascular remodeling. However, little is known about the pathogenic mechanisms underlying the disease onset and progression. RNA sequencing (RNA-seq) was used to identify the transcriptional profiling in control and rats injected with monocrotaline (MCT) for 1, 2, 3 and 4 weeks. A total of 23200 transcripts and 280, 1342, 908 and 3155 differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Our previous study has showed the elevated markers of macrophage infiltration and inflammatory mediators, such as TNFα and IL‐6, with concomitantly increased pulmonary arterial remodelling parameters WT% and WA% in the progression of MCT‐induced PAH 7 . RNA‐seq analysis of rat lungs isolated from control and MCT‐treated rats identified a total of 23 200 transcripts, of which 280, 1342, 908 and 3155 were differentially expressed at the end of weeks 1, 2, 3 and 4, respectively 10 . Further hierarchical clustering analysis of the differentially expressed genes (DEGs) revealed 10 clusters of expression pattern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study has showed the elevated markers of macrophage infiltration and inflammatory mediators, such as TNFα and IL‐6, with concomitantly increased pulmonary arterial remodelling parameters WT% and WA% in the progression of MCT‐induced PAH 7 . RNA‐seq analysis of rat lungs isolated from control and MCT‐treated rats identified a total of 23 200 transcripts, of which 280, 1342, 908 and 3155 were differentially expressed at the end of weeks 1, 2, 3 and 4, respectively 10 . Further hierarchical clustering analysis of the differentially expressed genes (DEGs) revealed 10 clusters of expression pattern.…”
Section: Resultsmentioning
confidence: 99%
“…9 We have performed RNA-seq analysis of rat lungs isolated from control and monocrotaline (MCT)-treated rats that had been treated with MCT for a variety of weeks, and this study showed that inflammatory and immune response was occurred at the early time-point of PAH development and dysregulated inflammation/immunity were involved in the onset and progression of PAH. 10 The changes of inflammation and immunity and pulmonary vascular remodelling that occur during the PAH progression largely result from the changes in the transcriptome. Therefore, in the current study, we use the RNA-seq data set and bioinformatics approach to carry out a further analysis of the transcriptome in MCT-induced PAH, aiming to have a deeper understanding of inflammatory and immune mechanisms in pulmonary vascular remodelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies evaluated the effects of PAs in gene expression in the lung or in human lung cells. Most of the studies focused on monocrotaline since this PA is often used to induce PAH in rats (Xiao et al 2020;Kishimoto et al 2015;Fu et al 2014). Therefore, the present study aimed to provide information which pathways are affected in rat lung after repeated-dose exposure to six structurally different PAs.…”
Section: Discussionmentioning
confidence: 99%
“…The phytotoxins can be found for example in Senecio jacobeae, which is resident in Western Europe, South Africa, Australia, New Zealand, and North America (Stegelmeier et al 1999). Furthermore, many other plants from families like Boraginaceae (all genera), Asteraceae (tribes Senecioneae and Eupatorieae) and Fabaceae contain PAs (Wiedenfeld et al 2008), which are produced as a defense mechanism against herbivores. They are synthesized in an estimated number of 6000 plant species and show a huge structural variety (EFSA 2011;Teuscher and Lindequist 2009).…”
Section: Introductionmentioning
confidence: 99%